Gabapentin versus dexchlorpheniramine as treatment for uremic pruritus: a randomised controlled trial - Gobo-Oliveira, Mariele [UNESP]; Pigari, Vitória G [UNESP]; Ogata, Matheus Sp [UNESP]; Miot, Hélio A [UNESP]; Ponce, Daniela [UNESP]; Abbade, Luciana Pf [UNESP] (JLE, 2018)
BACKGROUND: Uremic pruritus is a common symptom in chronic renal failure patients with undefined pathophysiology. Initial treatment involves topical therapy mainly in the form of moisturizers, however, in many cases, this is not sufficient to relieve itching. Systemic adjuvant therapy is therefore necessary, which commonly includes oral antihistamines, with limited success. Positive effects have been reported for gabapentin. OBJECTIVES: To evaluate the efficacy and safety of gabapentin vs. dexchlorpheniramine in reducing uremic pruritus. MATERIALS & METHODS: A randomized, controlled, double-blinded clinical trial for haemodialysis patients with persistent pruritus was performed. Pre-randomisation, cold cream was used for 15 days by 71 participants. Those with pruritus who remained in the study (60 patients) were randomised to receive gabapentin (30 patients; GABA group) or dexchlorpheniramine (30 patients; DEX group) for 21 days. The primary outcome was the decrease in pruritus score and improvement in quality of life. RESULTS: After cold cream use, the participants demonstrated a 37.5% median reduction in Visual Analogue Scale (p<0.01) and a 50% reduction in Quality of Life in Dermatology (DLQI) score (p<0.01). There was an additional reduction of pruritus in both groups (p<0.01), with no difference between the two (p>0.7). The median DLQI was reduced from 2 to 1 in the GABA group and from 2 to 0 in the DEX group. Nineteen patients (32%) reported mild/moderate side effects without differences between the groups. CONCLUSIONS: Uremic pruritus was reduced upon treatment with gabapentin or dexchlorpheniramine with good safety profiles; no difference was observed between the two treatments.
Keywords: cold cream; dexchlorpheniramine; gabapentin; haemodialysis; uremic pruritus